The impact of cognitive anxiety and stress on athletic performance: Educational programs and academic research for mental health - Kang, J. (ICERI2024 Proceedings, 2024)
In order to better understand how anxiety affects athlete psychology in competitive sports, this research will specifically look at the learning and instructional components of anxiety management. Athletes frequently suffer anxiety, which, depending on how it's handled, can either improve or impede performance. The study explores a number of psychological strategies that are crucial for helping athletes gain anxiety management skills, such as mindfulness-based treatments, cognitive-behavioral therapy (CBT), and visualization approaches. Examined is the function of coaches and support networks, focusing on how they affect athletes' capacity to become resilient and acquire useful coping skills.